Juvenile hormone and Broad-complex gene expression on programmed cell death in the anterior silk glands of the bamboo borer (omphisa fuscidentalis hampson) - Bunkuna,S. (Chiang Mai University, 2015)
© 2015 Chiang Mai University. All rights reserved. In insects, programmed cell death (PCD) causes the degeneration of larval-specific tissues during metamorphosis. The insect hormone involved in PCD is a steroid, 20- hydroxyecdysone (20E). This hormone induces PCD by stimulating several gene expressions including Broad-complex (BR-C). Since application of juvenile hormone analogue (JHA) induces pupation in diapausing larvae of the bamboo borer, Omphisa fuscidentalis, this research aimed to study the effects of juvenile hormone on PCD and the involvement of BR-C on the occurrence of PCD in the anterior silk glands (ASGs). Three concentrations of juvenile hormone analogue (JHA) were applied to diapausing larvae. The glands were collected on the different days during the treatment and stained with DAPI for observing morphological changes of cell and nucleus. Results showed that JHA was able to induce PCD in a dose response manner. In addition, a partial cDNA sequence was isolated from epidermis of G2-stage larvae with 636 base pair nucleotides. The similarity of Omphisa fuscidentalis BR-C with Manduca sexta BR-C and Bombyx mori BR-C was 77% and 73%, respectively. Moreover, anterior silk glands of JHA-treated larvae were dissected every 2 days until day 12 and from pupation stage (G0 to G3). cDNA from those anterior silk glands were prepared for determination of BR-C expression. Results showed that the expression of OfBR-C was transiently increased within 12 days of JHA treatment and decreased on the last day of pupation stage (G3). Because the expression pattern of OfBR-C induced by JHA was similar to the expression of Of Ecdysone receptor (EcR) induced by JHA as previously reported, suggesting that BR-C expression was involved with the expression of 20E-EcR signaling pathway.